PENERAPAN METODE CERTAINTY FACTOR PADA SISTEM PAKAR DIAGNOSA AWAL PENYAKIT HEWAN TERNAK KAMBING - Novhirtamely Kahar; Nela Lestari (JURNAL AKADEMIKA)
Initial diagnosis expert system of livestock disease of goats is a computer-based system that is used as a tool for initial diagnosis the diseases in goat that is based on a dynamic knowledge base. The knowledge base consists of the knowledge gained from various sources including from the experience of experts, those are veterinarians, breeders of goats, and also books related to the disease in livestock of goats which were later collected into a database that is required for making conclusions. In constructing this system the method used is Certainty Factor, with the input data including the value of certainty and uncertainty of clinical symptoms experienced by goats. A programming language used is Delphi 7 which is connected with a database of Microsoft Office Access 2007. Based on the study, the obtained results determined the disease in goats is based on the calculation of certainty and uncertainty symptoms experienced by goats, so the certainty Factor value for an illness suffered by animals such as goats stated as initial diagnosis.